A composite material of diphenylamine molecules and polyurethane with force-stimulation-responsive phosphorescence function and its preparation method and application
A diphenylamine-polyurethane composite material with enhanced phosphorescence and mechanical properties addresses the limitations of existing luminescent materials, offering reversible and sensitive force-stimulation responses for mechanical sensing and information storage.
Patent Information
- Application Number
- CN202410044145.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-01-12
AI Technical Summary
Existing luminescent materials lack the mechanical properties and processing properties required for practical applications, and most stimulus-responsive materials based on fluorescence have poor signal-to-noise ratio and low sensitivity, with irreversible or delayed mechanical responses.
A composite material is developed by physically blending diphenylamine (X-NP-Y) type derivatives with hydrogen-donating groups into polyurethane, enhancing hydrogen bonds and intersystem crossing efficiency to achieve reversible force-stimulation-responsive phosphorescence.
The composite material exhibits enhanced light-excited phosphorescence with increasing elongation, high mechanical strength, and excellent cycle stability, with a large luminescence signal-to-noise ratio and sensitivity, suitable for mechanical sensing, crack detection, and information storage.
Smart Images

Figure CN118388953B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of force stimulus responsive photoluminescent materials, and specifically relates to a composite material of diphenylamine molecules and polyurethane having a force stimulus responsive phosphorescent function, and a preparation method and application thereof. Background Art
[0002] Polymers have a wide range of properties, from simple rubber to high-performance plastics, and they all play an important role in people's daily lives. These polymers will inevitably be subjected to mechanical forces such as stretching, compression, shearing, and torsion during their application, resulting in irreversible damage to the materials. Therefore, if a material with force stimulus response can be developed to understand the location and time of damage, catastrophic material failure can be effectively avoided, which is of great value in material applications.
[0003] Both fluorescence and phosphorescence are optical phenomena in which the valence electrons of a material in the ground state absorb ultraviolet-visible light, undergo energy level transitions, undergo vibrational relaxation, reach the lowest vibrational energy level, and emit photons in the form of radiation. They can effectively transmit information as optical signals and have a wide range of applications in information encryption, bioimaging, and stimulus response. When valence electrons transition from the ground state to the various vibrational energy levels of the excited singlet state and quickly release a small amount of energy in the form of vibrational relaxation to reach the lowest vibrational energy level of the same excited state, the photons emitted in the form of radiation are called fluorescence. The afterglow time of fluorescence is generally less than 10 -8 s, basically, the emission stops immediately after the excitation stops. This type of emission is basically not affected by temperature. If the electrons of the excited molecule undergo spin reversal in the excited state, when the lower vibrational energy level of its singlet state overlaps with the higher energy level of the excited triplet state, intersystem crossing will occur, reaching the excited triplet state, and after vibrational relaxation, it will reach the lowest vibrational energy level, and then emit photons in the form of radiation to transition to any vibrational energy level of the ground state. The photons emitted at this time are called phosphorescence. The afterglow time of phosphorescence is generally greater than 10 -8 s, with the phenomenon of delayed luminescence. Using fluorescence or phosphorescence as a response signal for force stimulus response materials and detecting the effect of mechanical force through changes in light signals can effectively achieve the effect of predicting failures. It can also be used in various fields such as mechanical sensors, information storage and encryption.
[0004] Luminescent materials that are sensitive to external stimuli (such as force, heat, light, acid and alkali, etc.) have become a research hotspot because of their potential in applications such as information storage, anti-counterfeiting, and optoelectronic devices. At present, most stimulus-responsive luminescent materials are based on fluorescence, which has disadvantages such as poor signal-to-noise ratio and low sensitivity, and does not have the characteristics of delayed luminescence of phosphorescent materials. Therefore, the development of phosphorescent luminescent stimuli-responsive materials is of great significance. Moreover, existing organic phosphorescent materials are mainly obtained based on the crystallization-promoted phosphorescence mechanism of small molecules. The crystals are limited in practical applications due to poor mechanical properties and processing properties. The application of polymer materials in organic phosphorescent luminescence can improve the mechanical properties of the materials and give them good processing properties, making organic phosphorescent materials have greater application value. In addition, in most organic force stimulus response systems, the mechanical response is delayed or irreversible, and their luminescence cannot change quickly and repeatedly in multiple cycles of stress loading and release. In summary, one of the main research hotspots of current force stimulus response luminescent materials is how to develop phosphorescent polymer materials with reversible force response and excellent mechanical properties. Summary of the invention
[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention first designs and synthesizes a series of diphenylamine (X-NP-Y) type derivatives with hydrogen-donating groups, and then physically blends them into polyurethane with power-donating groups at a certain content to obtain a force-stimulation-responsive material. During the stretching process, the hydrogen bonds between the luminescent molecules and the polyurethane will be enhanced, thereby significantly enhancing the intensity of the light-excited phosphorescence and significantly prolonging the phosphorescence life, so that the material has force-stimulation-responsive performance, that is, the performance of light-excited phosphorescence enhancement with increasing elongation, and has a wide range of application potentials in the fields of mechanical sensing, crack detection, information storage and encryption.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a force stimulus responsive room temperature phosphorescent composite material, the composite material comprising an organic phosphorescent molecule and polyurethane, the organic phosphorescent molecule being a diphenylamine (X-NP-Y) type derivative having a hydrogen donating group, and the structural formula thereof is as follows:
[0008]
[0009] In the formula, X is selected from R1, R2, R3, R4, and R5 are independently selected from -H, -F, -Cl, -Br, -I, -Me, -OMe, -OEt, -CF3, -CN, -OH, -Ph, -NH2, -COOH, -COOCH3, -CHO, -COONa, -B(OH)2,
[0010] The present invention provides a composite material with sensitive force stimulus response phosphorescence and excellent mechanical cycle stability. This material can achieve the performance of light-excited phosphorescence enhancement with increasing elongation by simply physically blending specific luminescent molecules with elastic polyurethane. When the material is in a stress-free state or the elongation is very low, the room temperature phosphorescence of the material after ultraviolet light excitation is very weak and the life is very short; when the material is in a high elongation (greater than 100%), the material emits bright room temperature phosphorescence after ultraviolet light excitation, and the life is extended. Moreover, this change is reversible. After more than 100 stretching and stress release, the material still has excellent force stimulus response phosphorescence luminescence performance, and after continuous ultra-high elongation (400% or more) stretching for 25 hours, the phosphorescence performance is only slightly attenuated.
[0011] The present invention designs and synthesizes a series of diphenylamine (X-NP-Y) type derivatives with hydrogen supply groups, and the derivatives have excellent phosphorescent properties. When in a rigid environment, they can effectively reach the excited triplet state by ultraviolet light excitation electrons, and reduce non-radiative transitions to improve intersystem crossing efficiency, thereby obtaining bright phosphorescent luminescence. At the same time, this type of molecule contains a hydrogen supply group, which can form intermolecular hydrogen bonds with a substrate containing a power supply group, thereby reducing molecular vibration and stabilizing triplet excitation. It not only has excellent phosphorescent properties in a crystal environment, but also can maintain good phosphorescent properties in a polymer substrate or even in a flexible polymer material. At the same time, the polymer material used in the present invention covers various types of polyurethane (PU), which can not only provide a good pro-luminescent environment for luminescent molecules, but also has excellent mechanical properties (such as high elongation at break, tensile compression resilience, wear resistance, not easy aging, etc.) and processing properties (thermoplasticity, high decomposition temperature, good molding process, etc.), and has good biocompatibility and non-toxic characteristics, and has great application value.
[0012] Preferably, the polyurethane is selected from MDI / BDO / PBA-TPU, MDI / BDO / PCL-TPU, MDI / BDO / PPG-TPU, HDI / BDO / PTMG-TPU:
[0013]
[0014] The diisocyanate of the polyurethane of the present invention can be replaced by NDI, TDI, TODI, CHDI, TMDI, XDI, PPDI, IPDI and HTDI in addition to MDI and HDI, the chain extender can be replaced by EG, DEG, CHDM, PXG, HER and HQEE in addition to BDO, the oligomer diol can be replaced by PCL, PTMG and P(PO / EO) in addition to PBA and PPG, the hard segment content is 20%-60%, and the molecular weight of the oligomer diol is 1000-5000. In addition to TPU type polyurethane, other polyurethanes with tensile properties such as CPU type, WPU type and MPU type polyurethane are also in the composite film system. These polyurethanes can not only provide a good luminescence-promoting environment for luminescent molecules, but also have excellent mechanical properties (such as high elongation at break, tensile compression resilience, wear resistance and not easy aging, etc.) and processing properties (thermoplasticity, high decomposition temperature, good molding process, etc.), and have good biocompatibility and non-toxic characteristics, and have great application value.
[0015] Preferably, the organic phosphorescent molecule is selected from PHNP, PHNPBr, NANP, NANPO, TpNP, TpNPO, TpNPCOOH, TpNPP, TpNPCZ or TpNPCO:
[0016]
[0017] Diphenylamine (X-NP-Y) derivatives with hydrogen-donating groups have excellent phosphorescent properties. When in a rigid environment, they can effectively excite electrons to the excited triplet state through ultraviolet light, reduce non-radiative transitions and improve intersystem crossing efficiency, thereby obtaining bright phosphorescent light. At the same time, this type of molecule contains hydrogen-donating groups, which can form intermolecular hydrogen bonds with substrates containing power-donating groups, reduce molecular vibrations and stabilize triplet excitations. They not only have excellent phosphorescent properties in a crystal environment, but also can maintain good phosphorescent properties in polymer substrates and even flexible polymer materials.
[0018] The second aspect of the present invention provides a method for preparing the force stimulus responsive room temperature phosphorescent composite material described in the first aspect, specifically comprising: dissolving organic phosphorescent molecules and polyurethane in an organic solvent, mixing them well and then heating to remove the solvent.
[0019] Preferably, the amount of the organic phosphorescent molecules is 0.1-10 wt.% of the polyurethane.
[0020] Preferably, the mixing is stirring at room temperature for 3-8 hours.
[0021] Preferably, the organic solvent includes (but is not limited to) acetone, ethyl acetate, THF, DMF and DMSO. The temperature for heating to remove the solvent is determined by the boiling point of the selected organic solvent.
[0022] The third aspect of the present invention provides applications of the force stimulus responsive room temperature phosphorescent composite material described in the first aspect, and the application fields include (but are not limited to) mechanical sensing, crack detection, information storage and encryption, and flexible wearables.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] At present, most stimulus-responsive luminescent materials are based on fluorescence, which has the disadvantages of poor signal-to-noise ratio and low sensitivity, and does not have the characteristics of delayed luminescence of phosphorescent materials. In addition, existing phosphorescent materials are mainly obtained based on the aggregation-induced luminescence mechanism of crystals. Crystals are limited in practical application due to poor mechanical properties and processing properties. The application of polymer materials in organic phosphorescent luminescence can improve the mechanical properties and processing properties of materials, making the types of mechanical forces that materials can withstand more extensive and more practical. To this end, the present invention uses elastic polyurethane as a substrate, and physically mixes organic phosphorescent molecules into elastic polyurethane, thereby achieving the performance of light-excited phosphorescence enhancement with increasing elongation, so that the material obtains superior mechanical properties and force-stimulated phosphorescent response sensitivity. The diphenylamine molecule and polyurethane composite material of the present invention has good thermoplasticity, can be molded into various shapes for application in various scenarios, and has excellent tensile properties, with an elongation at break of about 500%-800%, and the organic phosphorescent molecules therein have excellent phosphorescent luminescence performance and strong force-stimulated responsiveness. In addition, in most organic force stimulus response systems, the mechanical response is delayed or irreversible, and their luminescence cannot be changed quickly and repeatedly in multiple cycles of stress loading and release. However, the diphenylamine molecule and polyurethane composite material of the present invention not only has high phosphorescence brightness, but also has excellent mechanical cycle stability. After more than 100 stretching and stress release, the material still has excellent force stimulus response phosphorescence luminescence performance, and after continuous ultra-high elongation (400% or more) stretching for 25 hours, the phosphorescence performance is only slightly attenuated.
[0025] It can be seen that the composite film material doped with diphenylamine organic phosphorescent molecules and polyurethane provided by the present invention is a composite material whose light-excited phosphorescence can be enhanced as the elongation increases. The material exhibits a force stimulation response based on phosphorescence changes, has the advantages of a large luminescence signal-to-noise ratio and high sensitivity, and has high mechanical strength and excellent tensile properties, processing and molding properties, reversible recovery properties, etc. At the same time, its phosphorescence changes instantaneously with changes in mechanical force, is reversible and has no hysteresis, has good mechanical cycle stability, and has broad application potential in the fields of mechanical sensing, crack detection, information storage and encryption. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1This is an image of a polyurethane composite film at an elongation of 400%. The composite film is a transparent film, and the two ends are clamps for fixing the elongation state of the sample.
[0027] Figure 2 This is an image of the afterglow emitted by the polyurethane composite film during the stretching and stress release process. The elongation is given in percentage, which is divided into the elongation during the elongation and stress release process. The afterglow time unit is s.
[0028] Figure 3 The images of the phosphorescence emitted by the polyurethane composite film during the stretching and stress release process change with the elongation rate; (a) phosphorescence spectrum during the stretching process, (b) phosphorescence spectrum during the stress release process; the excitation wavelength used in the spectral test is 365nm, and the arrows above and below represent the stretching and stress release processes, respectively;
[0029] Figure 4 The phosphorescence spectra of other polyurethane composite films; (a) the phosphorescence spectrum of TpCOP as the stretching process of phosphorescent molecules, (b) the phosphorescence spectrum of TpB as the stretching process of phosphorescent molecules;
[0030] Figure 5 Phosphorescence spectra of other polymer composite films; (a) Phosphorescence spectrum of NANPO@EVOH during stretching, (b) Phosphorescence spectrum of PHNPO@EVOH during stretching. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0033] Example 1 Synthesis of diphenylamine organic phosphorescent molecules
[0034]
[0035] According to formula (I) or formula (II), prepare a 250mL three-necked flask, add raw materials 2-bromobenzo[9,10]phenanthrene (500mg, 1.63mmol) and aniline (138mg, 1.48mmol), add catalyst tri(dibenzylideneacetone)dipalladium (Pd2(dba)3, 68mg, 0.07mmol) and metal complex potassium dihydrogen diphosphate (dppf, 41mg, 0.07mmol), and add tert-butyl potassium oxide (t-BuONa, 142mg, 1.48mmol) to the system. Then, add 40mL of toluene to the above reaction system, firstly bubble nitrogen for 30min to remove the air in the system, then heat to 80℃, and stir the reaction at this temperature in a nitrogen atmosphere for about 24h. After the reaction was completed, the mixture was naturally cooled to room temperature, the product was concentrated and separated by column chromatography to obtain the final products TpNP and TpNPO (yields were 60% and 70%, respectively). Finally, the product was purified by recrystallization and dried in a vacuum oven at 65°C for 4 h to obtain a dry powder.
[0036] The H-NMR spectrum data of TpNP are as follows:
[0037] 1 H NMR (400MHz, DMSO-d6) δ8.83–8.72(m,2H),8.66(dt,J=10.7,5.8Hz,3H),8.52(dt,J=6.1,3.2Hz,1H),8.33(d,J=2.3Hz, 1H),7.73–7.57(m,4H),7.48(dd,J=8.9,2.3Hz,1H),7.35(dd,J=8.5,7.1Hz,2H),7.31–7.23(m,2H),6.98–6.91(m,1H).
[0038] The H-NMR spectrum data of TpNPO are as follows:
[0039] 1 H NMR(400MHz,DMSO-d6)δ8.75(ddd,J=17.7,7.4,2.4Hz,2H),8.65–8.57(m,2H),8.44(dt,J=6.9,3.5Hz,1H),8.33(s,1H), 8.15(d,J=2.3Hz,1H),7.72–7.55(m,4H),7.33(dd,J=8.9,2.3Hz,1H),7.29–7.20(m,2H),7.03–6.94(m,2H),3.78(s,3H).
[0040] Example 2 Preparation of polyurethane composite film
[0041] (1) 1 g of polyurethane (MDI / BDO / PBA-TPU, Mn=33800, PDI=1.28) and 10 mg of organic phosphorescent molecules (TpNP or TpNPO) were dissolved in THF and stirred at room temperature for 4 h to 5 h for physical blending (phosphorescent molecules accounted for 1 wt.%);
[0042]
[0043] (2) drying the mixed solution in a 65°C forced air oven for 6 h, and then drying it in a 65°C vacuum oven for 6 h to further remove the solvent;
[0044] (3) The mixture after solvent removal is placed in a specific mold, and then hot-pressed at 160° C. for 5 min in a hot press, and a transparent and smooth polyurethane composite film is obtained after cooling.
[0045] For the convenience of testing and use, the polyurethane composite film was prepared into a barbell shape (total length 5 cm, length of the stretched part 3 cm, width 1 cm, thickness 0.2 mm), as shown in FIG. Figure 1 As shown, the polyurethane composite film can be stretched to a set elongation and fixed.
[0046] Experimental Example 1 Phosphorescence Performance Test of Polyurethane Composite Film
[0047] The polyurethane composite film prepared in Example 2 was stretched at a certain elongation rate, and then the stress was released to gradually restore the length of the film. In this process, a 365nm LED light source was used for excitation, and it was observed that the composite film emitted afterglow with different brightness and afterglow time at different elongation rates. Figure 2 As shown in the figure, during the stretching process, the afterglow gradually increases and the afterglow time gradually prolongs as the elongation increases; during the stress release process, the afterglow gradually weakens and the afterglow time gradually shortens as the elongation decreases.
[0048] At the same time, the phosphorescence spectrum of the polyurethane composite film was tested by the spectrometer system (MayaPro2000) of Ocean Optics, and the excitation source was a 365nm LED light source. Figure 3 As shown, the composite film is stretched to different elongations and fixed, and its photoexcited phosphorescence spectrum is tested. It can be found that the phosphorescence increases with the increase of elongation, while the phosphorescence weakens with the release of stress. After the stress is completely released, the phosphorescence intensity returns to the level before stretching.
[0049] pass Figure 2 , 3 It can be seen that the polyurethane composite film prepared by the present invention has excellent mechanical strength and tensile properties ( Figure 1), the shape is plastic and the elongation at break is over 400%, which provides great convenience for its practical application. At the same time, the afterglow change of the force stimulation response is clearly visible to the naked eye ( Figure 2 ), the brightness and duration of the afterglow are significantly correlated with the change in mechanical force, ensuring the sensitivity and reliability of the stimulus response. In addition, its phosphorescence intensity is closely related to the mechanical force ( Figure 3 ), proving that it is a force stimulus responsive phosphorescent material with superior performance. It can be seen that the present invention achieves the effect of enhancing the room temperature phosphorescence under stretching by doping organic phosphorescent molecules into polyurethane to make a composite material. As the elongation of the composite film increases, the room temperature phosphorescence intensity generated by the composite film under the excitation of a 365nm ultraviolet light source gradually increases and the life span gradually increases.
[0050] In addition, in order to further study the scope of application of the present invention, the same method as in the embodiment is used to physically blend molecules (TpCOP, TpB) with excellent phosphorescent properties (see "Lin F, Wang H, Cao Y, et al. Stepwise Energy Transfer: Near-Infrared Persistent Luminescence from Doped Polymeric Systems [J]. Advanced materials (Deerfield Beach, Fla.), 2022, 34 (15): e2108333. DOI: 10.1002 / adma.202108333.") into polyurethane, and the composite film is prepared into an in-situ tensile test as a control. Figure 4 As shown, although TpCOP and TpB have strong light-stimulated phosphorescence in polymers such as PMMA and PVA when physically blended, they basically do not emit phosphorescence when mixed into polyurethane, and after stretching, they do not have the property of enhanced light-stimulated phosphorescence with increasing elongation.
[0051] At the same time, the phosphorescent molecules used in the example were physically blended into EVOH (ethylene-vinyl alcohol copolymer) to prepare a composite film using the same method as in the example, and its in-situ stretched phosphorescence spectrum was tested as a control. Figure 5 As shown, the phosphorescent molecules of the present invention are physically blended into EVOH. Although the phosphorescent luminescence performance is good, the phosphorescent intensity decreases as the elongation increases because the composite film becomes thinner, and the film does not have the performance of enhanced phosphorescence after light excitation after stretching.
[0052] Through the above comparison, it can be seen that the present invention has unique requirements for the phosphorescent molecular structure and polymer structure. It is not possible to simply dope a material with phosphorescent luminescence properties with a polymer with mechanical properties and processing properties to obtain a force stimulus responsive phosphorescent material, but it requires that the host and the guest meet the structural requirements at the same time. At the same time, the physical blending method and composite film preparation scheme of the present invention are both conducive to the composite material showing the best force stimulus performance, which is simple and practical.
[0053] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A force stimulus responsive room temperature phosphorescent composite material, characterized in that: The composite material comprises an organic phosphorescent molecule and polyurethane, wherein the organic phosphorescent molecule is a diphenylamine derivative having a hydrogen-donating group, and its structural formula is as follows: In the formula, X is selected from R1, R2, R3, R4, and R5 are independently selected from -H, -F, -Cl, -Br, -I, -Me, -OMe, -OEt, -CF3, -CN, -OH, -NH2, -COOH, -COOCH3, -CHO, -COONa, and -B(OH)2.
2. The force stimulus responsive room temperature phosphorescent composite material according to claim 1, characterized in that: The polyurethane is composed of diisocyanate, oligomer diol and chain extender, wherein the diisocyanate is selected from MDI, HDI, 2,4-TDI, 2,6-TDI, PPDI, CHDI, NDI, IPDI or PAPI, and PAPI is a mixture of 50% MDI and 50% polyisocyanate with a functionality greater than 2; the oligomer diol is selected from PBA, PCL, PTMG, PPG or P(PO / EO); the chain extender is selected from BDO, EG, DEG, 1,6-HDO, CHDM, PXG, HQEE or HER:
3. The force stimulus responsive room temperature phosphorescent composite material according to claim 1, characterized in that: The organic phosphorescent molecule is selected from TpNP, TpNPO or TpNPCOOH 4. The method for preparing the force stimulus responsive room temperature phosphorescent composite material according to any one of claims 1 to 3, characterized in that: The organic phosphorescent molecules and polyurethane are dissolved in an organic solvent, mixed well, and then heated to remove the solvent.
5. The method for preparing the force stimulus responsive room temperature phosphorescent composite material according to claim 4, characterized in that: The amount of the organic phosphorescent molecules used is 0.1-10 wt.% of the polyurethane.
6. The method for preparing the force stimulus responsive room temperature phosphorescent composite material according to claim 4, characterized in that: The mixing is carried out at room temperature for 3-8 hours.
7. The method for preparing the force stimulus responsive room temperature phosphorescent composite material according to claim 4, characterized in that: The organic solvents include acetone, ethyl acetate, THF, DMF and DMSO.
8. Use of the force stimulus responsive room temperature phosphorescent composite material according to any one of claims 1 to 3, characterized in that: Application areas include mechanical sensing, crack detection, information storage and encryption, and flexible wearables.
